I've changed, I really have: identity, regime change and ontological security. Issue 2 (4th May 2019) - Mahant, Edelgard
ABSTRACT: Constructivists have coined the phrase "ontological security", implying that a state's sense of national identity is as or more important than its physical characteristics in shaping its foreign policy. But what happens to foreign policy when that sense of identity changes as the result of a revolution or regime change so extreme that the previous national identity no longer holds? Using the example of South Africa after the end of apartheid, this article examines the attempts by the leaders of post-apartheid governments to create a new national identity, based on South Africa's new status as a democratic country and as a country whose destiny is in Africa. The article finds that the governments succeeded in establishing the beginnings of the second but not the first of these new identities.